Water-resistant polyvinyl alcohol coating system and preparation method thereof
Through solvent replacement method and mechanical blending technology, a polyvinyl alcohol coating system doped with nitrocellulose nanoparticles was prepared, which solved the problem of water absorption restriction of PVA, and achieved an improved water resistance and environmentally friendly and low-cost preparation process.
Patent Information
- Application Number
- CN202411920283.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-02-25
AI Technical Summary
Due to its severe water absorption, polyvinyl alcohol (PVA) limits its wide application in drug coating, slow-controlled release of fertilizers and food packaging. The existing modification methods are complex in technology, high in cost and severe environmental pollution.
The solvent replacement method is used to obtain a nanocomposite coating system without adding an emulsifier, and then a nanocomposite coating system is prepared by mechanical blending and compounded with PVA aqueous solution.
It achieves improved water resistance of PVA, does not require complex process equipment and toxic solvents, is simple to operate and environmentally friendly, reduces preparation costs and improves product biocompatibility.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a water-resistant polyvinyl alcohol coating system and a preparation method thereof. More specifically, the present invention relates to a method for preparing a water-resistant polyvinyl alcohol aqueous coating system by doping with nitrocellulose nanoparticles. Background Art
[0002] Polyvinyl alcohol (PVA) is a white, odorless, biocompatible and thermally stable water-soluble granular polymer. It has excellent film-forming properties, mechanical properties and good interfacial adhesion, and has been widely used in drug coating, fertilizer controlled release and food packaging. In addition, PVA is also an excellent non-ionic surfactant, which is often used in the preparation of emulsions and aqueous dispersions to improve the stability of the system. However, due to the serious water absorption of PVA itself, it is subject to many restrictions during use, which seriously hinders its wide application. At present, chemical methods are usually used to introduce hydrophobic groups into the PVA molecular chain to inhibit its water absorption, but this method is complex and costly, and it also has serious environmental pollution, poor product comprehensive performance and difficulty in film formation. Nitrocellulose (NC) is a bioplastic widely used in adhesives, coatings and other fields. It has excellent characteristics such as low production cost, excellent film-forming properties, moisture absorption resistance and environmental friendliness. Then, doping it into PVA as a modified filler has become an effective method to regulate the hygroscopicity of PVA. However, since NC is insoluble in water and has a large size, it is difficult to disperse it evenly in the PVA system. How to prepare this composite material has become a research focus and difficulty.
[0003] Based on this, the present invention adopts a simple-to-operate, environmentally friendly solvent replacement method to first obtain NC nano water dispersion without the participation of an external emulsifier, and then compound it with a PVA aqueous solution through mechanical blending to obtain a nanocomposite coating system, in order to achieve the preparation of a hygroscopically resistant PVA coating system. Summary of the invention
[0004] The object of the present invention is to solve the above-mentioned deficiencies of the prior art, thereby providing a method for preparing a water-resistant polyvinyl alcohol coating system, which does not require a complicated preparation process and can achieve a method for uniformly mixing water-insoluble NC and water-soluble PVA by a solvent replacement method.
[0005] A method for preparing a water-resistant polyvinyl alcohol coating system comprises the following steps: Preparation of PVA aqueous solution: PVA was weighed, added into deionized water, dissolved under continuous heating and stirring to form a transparent solution, and allowed to stand and cool; Preparation of NC solution: Weigh NC and add it to a mixed solution of ethanol and acetone under continuous stirring, and continue stirring until NC is completely dissolved to form a uniform NC solution; Emulsification: under continuous heating and stirring, the prepared NC solution is added to the prepared PVA aqueous solution in a certain volume ratio, and stirring is continued to obtain a milky white and blue-light crude emulsion through solvent replacement; Solvent removal: The crude emulsion is added into a rotary evaporator bottle, and the organic solvent in the crude emulsion is removed by the rotary evaporator under reduced pressure to prepare a water-resistant polyvinyl alcohol coating system doped with NC nanoparticles.
[0006] The preparation of PVA aqueous solution is specifically as follows: Add 0.05-0.8 g of polyvinyl alcohol to 10±1 mL of deionized water, dissolve under continuous magnetic stirring at 80-100° C. to form a transparent solution, and allow to cool to prepare a PVA aqueous solution with a concentration of 5 mg / mL-80 mg / mL.
[0007] In the preparation of the PVA aqueous solution, the stirring speed is 300~500rpm and the stirring time is 3~5h.
[0008] The preparation of NC solution is as follows: 0.2 g of NC was added to 10 ± 1 mL of a mixed solvent of acetone and ethanol with a volume ratio of acetone to ethanol of 10:0 to 2:8. The solution was continuously stirred magnetically at 300 to 500 rpm for 15 to 30 min to prepare a uniform NC solution with a concentration of 20 mg / ml.
[0009] In the preparation of NC solution, the nitrogen content of NC is 11.8~12%.
[0010] Emulsification is specifically: At a temperature of 28±1°C and under continuous magnetic stirring at 300~500 rpm, the prepared NC solution was added to the PVA aqueous solution to form an oil-water mixed phase. The volume ratio of the NC solution to the PVA aqueous solution was 1:1. The oil-water mixed phase was continuously stirred for 20±2 min to obtain a milky white and bluish crude emulsion.
[0011] During solvent removal, The reduced pressure conditions refer to a temperature of 35~40°C and a pressure of -0.098 MPa.
[0012] Another aspect of the present invention provides a water-resistant polyvinyl alcohol coating system prepared by the method for preparing the water-resistant polyvinyl alcohol coating system described in the above scheme.
[0013] Another aspect of the present invention provides a method for preparing a water-resistant polyvinyl alcohol nanocomposite film using the water-resistant polyvinyl alcohol coating system described in the above scheme, characterized in that it comprises the following steps: The water-resistant polyvinyl alcohol aqueous coating system according to claim 8 is uniformly cast onto a container, and then placed in a water bath oven at 50-60° C. and dried for 24-36 hours.
[0014] The present invention uses nitrocellulose alcohol ketone solution as the oil phase and polyvinyl alcohol aqueous solution as the water phase, and uses a solvent replacement method to mix the two to prepare a polyvinyl alcohol nanocomposite coating system, and uses a drying method to prepare a corresponding polyvinyl alcohol composite film. Using a simple solvent replacement method, NC nanoparticles are doped into PVA to prepare a moisture-resistant PVA coating system. The research process is simple to operate, environmentally friendly, low-cost, short in processing time, and has good product effects.
[0015] Compared with the prior art, the present invention has at least the following advantages: (1) The present invention uses low-cost, biodegradable NC as a hygroscopic filler, which effectively reduces the preparation cost, realizes green manufacturing of the product, and effectively improves the biocompatibility and environmental friendliness of the product; (2) The present invention uses a solvent replacement method to dope the hygroscopic NC filler into PVA to improve its hygroscopic resistance. It does not require the complex equipment, complex processes and a large amount of toxic and harmful solvents involved in the traditional chemical modification method. The whole process is simple to operate and has good reproducibility. The present invention prepares a polyvinyl alcohol aqueous coating system doped with nitrocellulose nanoparticles by a simple solvent replacement method without using any complex equipment. The film obtained after drying has good hygroscopic resistance and biocompatibility, which solves the problems of complex operation, poor reproducibility, serious environmental pollution, high cost and the like in the traditional preparation method of the water-resistant polyvinyl alcohol aqueous coating system. It provides a new method for simply preparing a polyvinyl alcohol coating system with good biocompatibility and hygroscopic resistance, and is expected to be applied to surface protection and encapsulation in the fields of urea, cosmetics, food and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The macroscopic morphology of the PVA coating system prepared in the examples and comparative examples after drying; Figure 2 The microstructure of the film formed after drying of the PVA aqueous coating system prepared in the examples and comparative examples; Figure 3 The bar graph is a saturated moisture absorption bar of the PVA coating system prepared in the examples and comparative examples at a relative humidity of 90%. DETAILED DESCRIPTION
[0017] The technical solution provided by the present invention is described in detail below in conjunction with embodiments. It should be understood that the following specific implementation methods are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0018] In a first aspect, the present invention provides a method for preparing a water-resistant polyvinyl alcohol coating system by doping with nitrocellulose nanoparticles, which specifically involves the following steps: Step 1: Preparation of PVA aqueous solution: Accurately weigh a certain mass of PVA, add it into a round-bottom flask filled with deionized water, dissolve it at a certain heating temperature and under continuous magnetic stirring to form a transparent solution, and let it stand to cool; Step 2: Preparation of NC solution: Accurately weigh a certain mass of NC, add it into a mixed solution of ethanol and acetone under continuous magnetic stirring, and continue stirring for a certain period of time to completely dissolve NC and form a uniform solution; Step 3, emulsification: at a certain temperature, under continuous magnetic stirring, add the NC solution prepared in the second step to the PVA aqueous solution obtained in the first step according to a certain volume ratio, continue stirring for a certain period of time, and obtain a milky white and blue-light crude emulsion through solvent replacement; Step 4: solvent removal: the crude emulsion prepared in the third step is added into a rotary evaporator, and the organic solvent in the crude emulsion is removed by a rotary evaporator under reduced pressure to prepare a NC nanoparticle-doped PVA aqueous coating system.
[0019] Furthermore, the mass of the PVA described in the first step is 0.05-0.8 g, the deionized water is 10 ± 1 mL, the stirring speed is 300-500 rpm, the stirring temperature is 80-100 ° C, the stirring time is 3-5 h, and the concentration of the prepared PVA aqueous solution is 5 mg / mL-80 mg / mL; Furthermore, the nitrogen content of the NC described in the second step is 11.8-12%, the mass is 0.2 g, the volume ratio of ethanol to acetone is 10:0-2:8, the total volume is 10±1 mL, the stirring speed is 300-500 rpm, the stirring time is 15-30 min, and the concentration of the prepared NC solution is 20 mg / mL; Furthermore, the preparation temperature described in the third step is 28 ± 1 °C, the volume ratio is 1:1, the stirring speed is 300-500 rpm, and the stirring time is 20 ± 2 min; Furthermore, the reduced pressure conditions described in the fourth step are 40°C, -0.098 MPa, and the mass fraction of NC in the prepared system is 20%~80%.
[0020] In a second aspect, the present invention provides a water-resistant polyvinyl alcohol coating system prepared by the method for preparing a water-resistant polyvinyl alcohol coating system described in the above technical solution.
[0021] In a third aspect, the present invention provides a method for preparing a water-resistant polyvinyl alcohol nanocomposite film using the water-resistant polyvinyl alcohol coating system described in the above technical solution, characterized in that it comprises the following steps: The water-resistant polyvinyl alcohol aqueous coating system described in the above scheme is uniformly cast onto the container, and then placed in a water bath oven at 50-60° C. to dry for 24-36 hours. Example 1
[0022] Aspect 1: Preparation of PVA coating system doped with 50% NC by mass (1) Add 0.2 g of PVA to 10 mL of deionized water, stir at 500 rpm at 85 °C for 5 h to dissolve to form a transparent solution, and let it stand to cool to prepare a PVA aqueous solution with a concentration of 20 mg / mL.
[0023] (2) Add 0.2 g of NC into 10 mL of a mixed solvent of acetone and ethanol (the volume ratio of acetone to ethanol is 2:3) and stir at 300 rpm for 30 min to prepare a homogeneous NC solution with a concentration of 20 mg / ml.
[0024] (3) At a temperature of 27°C, 10 mL of the prepared NC solution was added to 10 mL of the PVA aqueous solution and mixed continuously for 22 min under mechanical stirring at 500 rpm to obtain a milky white crude emulsion with a bluish luster.
[0025] (4) Add 20 mL of the prepared crude emulsion into a 100 mL rotary evaporator, and remove the organic solvent in the crude emulsion using a rotary evaporator under reduced pressure conditions (40 °C, -0.098 MPa) to prepare a PVA aqueous coating system with an NC mass fraction of 50%.
[0026] Second aspect: Characteristic test of PVA coating system (1) 5 g of the PVA aqueous coating system prepared in Example 1 was uniformly cast into a glass culture dish with a diameter of 60 mm, and then placed in a water bath oven at 60° C. and dried for 24 hours to obtain a water-resistant polyvinyl alcohol nanocomposite film.
[0027] (2) The surface macroscopic and microscopic morphologies of the water-resistant polyvinyl alcohol nanocomposite film prepared by the coating system of Example 1 were observed using a digital camera and a scanning electron microscope, respectively. The results are shown in the accompanying drawings. Figure 1 The macroscopic structure and shape of the PVA coating system with 3#NC content of 50% after drying Figure 2(f) Microstructure of the film formed after drying of the PVA aqueous coating system with NC content of 50% and (g) A magnified view of the microstructure of the film formed after drying of the PVA aqueous coating system with NC content of 50%. It can be seen from the figure that the prepared film is complete and dense, and the NC particles are evenly dispersed in the PVA without obvious agglomeration.
[0028] (3) The saturated moisture absorption capacity (EMC) of the water-resistant polyvinyl alcohol nanocomposite film prepared by the coating system of Example 1 at 90% relative humidity was measured using a dynamic vapor sorption instrument (DVS). The results are shown in the accompanying figure. Figure 3 The bar graph of the saturated moisture absorption of the PVA coating system with 50% NC content at 90% relative humidity. It can be seen from the figure that after being doped with NC particles, the saturated moisture absorption of PVA at 90% relative humidity is Figure 3 The saturated moisture absorption bar graph of the PVA coating system with 0% 6#NC content at 90% relative humidity decreased from 24.90% to 14.25%, a decrease of about 43%. Example 2
[0029] Aspect 1: Preparation of PVA coating system doped with 33% NC by mass (1) Add 0.4 g of PVA to 10 mL of deionized water, stir at 400 rpm for 4 h at 90 °C to dissolve to form a transparent solution, and let it stand to cool to prepare a PVA aqueous solution with a concentration of 18 mg / mL.
[0030] (2) Add 0.2 g of NC into 10 mL of a mixed solvent of acetone and ethanol (the volume ratio of acetone to ethanol is 10:0) and stir at 400 rpm for 20 min to prepare a homogeneous NC solution with a concentration of 20 mg / ml.
[0031] (3) At 29°C, add 10 mL of the prepared NC solution into 10 mL of PVA aqueous solution and continue mixing under mechanical stirring at 500 rpm for 20 min to obtain a milky white crude emulsion with a bluish glow.
[0032] (4) Add 20 mL of the prepared crude emulsion into a 100 mL rotary evaporator and remove the organic solvent in the crude emulsion using a rotary evaporator under reduced pressure (40°C, -0.098 MPa) to prepare a PVA aqueous coating system with an NC mass fraction of 33%.
[0033] Second aspect: Characteristic test of PVA coating system (1) 5 g of the PVA aqueous coating system prepared in Example 2 was uniformly cast into a glass petri dish with a diameter of 60 mm, and then placed in a water bath oven at 55° C. and dried for 30 hours to obtain a water-resistant polyvinyl alcohol nanocomposite film.
[0034] (2) The surface macroscopic and microscopic morphologies of the water-resistant polyvinyl alcohol nanocomposite film prepared by the coating system of Example 2 were observed using a digital camera and a scanning electron microscope, respectively. The results are shown in the accompanying drawings. Figure 1 The macroscopic structure and shape of the PVA coating system with 4#NC content of 33% after drying Figure 2 (d) The microstructure of the film formed after drying of the PVA aqueous coating system with NC content of 33% and (e) The enlarged microstructure of the film formed after drying of the PVA aqueous coating system with NC content of 33%. It can be seen from the figure that the prepared film is complete and dense, and the NC particles are evenly dispersed in the PVA without obvious agglomeration.
[0035] (3) The saturated moisture absorption capacity (EMC) of the water-resistant polyvinyl alcohol nanocomposite film containing the coating system of Example 2 at 90% relative humidity was measured using a dynamic vapor sorption instrument (DVS). The results are shown in the accompanying figure. Figure 3 The bar graph of the saturated moisture absorption of the PVA coating system with 4#NC content of 33% at 90% relative humidity. It can be seen from the figure that after being doped with NC particles, the saturated moisture absorption of PVA at 90% relative humidity is Figure 3 The saturated moisture absorption bar graph of the PVA coating system with 0% 6#NC content at 90% relative humidity decreased from 24.90% to 17.28%, a decrease of about 31%. Example 3
[0036] Aspect 1: Preparation of PVA coating system doped with 20% NC by mass (1) Add 0.8 g of PVA to 10 mL of deionized water and stir at 300 rpm for 3 h at 100 °C to dissolve to form a transparent solution. Let it stand and cool to prepare a PVA aqueous solution with a concentration of 80 mg / mL.
[0037] (2) Add 0.2 g of NC into 10 mL of a mixed solvent of acetone and ethanol (the volume ratio of acetone to ethanol is 2:8) and stir at 500 rpm for 15 min to prepare a homogeneous NC solution with a concentration of 20 mg / ml.
[0038] (3) At 28°C, add 10 mL of the prepared NC solution into 10 mL of PVA aqueous solution and continue mixing under mechanical stirring at 500 rpm for 20 min to obtain a milky white crude emulsion with a bluish glow.
[0039] (4) Add 20 mL of the prepared crude emulsion into a 100 mL rotary evaporator and remove the organic solvent in the crude emulsion using a rotary evaporator under reduced pressure (40°C, -0.098 MPa) to prepare a PVA aqueous coating system with an NC mass fraction of 50%.
[0040] Second aspect: Characteristic test of PVA coating system (1) 5 g of the PVA aqueous coating system prepared in Example 3 was uniformly cast into a glass culture dish with a diameter of 60 mm, and then placed in a water bath oven at 50° C. and dried for 36 hours to obtain a water-resistant polyvinyl alcohol nanocomposite film.
[0041] (2) The macroscopic and microscopic morphologies of the surface of the water-resistant polyvinyl alcohol nanocomposite film prepared by the coating system of Example 3 were observed using a digital camera and a scanning electron microscope, respectively. The results are shown in the accompanying drawings. Figure 1 The macroscopic structure and shape of the PVA coating system with 5#NC content of 20% after drying Figure 2 (b) The microstructure of the film formed after drying of the PVA aqueous coating system with NC content of 20% and (c) the enlarged microstructure of the film formed after drying of the PVA aqueous coating system with NC content of 33%. It can be seen from the figure that the prepared film is complete and dense, and the NC particles are evenly dispersed in the PVA without obvious agglomeration.
[0042] (3) The saturated moisture absorption capacity (EMC) of the water-resistant polyvinyl alcohol nanocomposite film prepared by the coating system of Example 3 at 90% relative humidity was measured using a dynamic vapor sorption instrument (DVS). The results are shown in the accompanying figure. Figure 3 The bar graph of the saturated moisture absorption of the PVA coating system with 5# NC content of 20% at 90% relative humidity. It can be seen from the figure that after being doped with NC particles, the saturated moisture absorption of PVA at 90% relative humidity is Figure 3 The saturated moisture absorption capacity of the PVA coating system with 0% 6#NC content at 90% relative humidity decreased from 24.90% to 19.24%, a decrease of about 23%.
[0043] Figure 1 #6 in the figure is the macroscopic morphology structure of the PVA aqueous coating system with NC content of 0% after drying.
[0044] Figure 2 (a) shows the microstructure of the film formed after drying of the PVA aqueous coating system with NC content of 0%.
[0045] Figure 3 0# in the figure is the bar graph of saturated moisture absorption of NC at 90% relative humidity.
[0046] The present application also provides a water-resistant polyvinyl alcohol nanocomposite film prepared by the method for preparing a water-resistant polyvinyl alcohol nanocomposite film described in the above scheme.
[0047] The present invention utilizes a simple solvent replacement method in combination with nitrocellulose nanoparticles to improve the water resistance of polyvinyl alcohol. The present invention prepares a polyvinyl alcohol aqueous coating system doped with nitrocellulose nanoparticles by a simple solvent replacement method without using any complex equipment. The film obtained after drying has good hygroscopic resistance and biocompatibility, which solves the problems of complex operation, poor reproducibility, serious environmental pollution, high cost, etc. in the traditional preparation method of water-resistant polyvinyl alcohol aqueous coating system, and provides a new method for simply preparing a polyvinyl alcohol coating system with good biocompatibility and hygroscopic resistance, which is expected to be applied to surface protection and encapsulation in the fields of urea, cosmetics, food, etc.
Claims
1. A method for preparing a water-resistant polyvinyl alcohol coating system, characterized in that: The following steps are involved: Preparation of PVA aqueous solution: PVA was weighed, added into deionized water, dissolved under continuous heating and stirring to form a transparent solution, and allowed to stand and cool; Preparation of NC solution: Weigh NC and add it to a mixed solution of ethanol and acetone under continuous stirring. Continue stirring until NC is completely dissolved to form a uniform NC solution. Emulsification: under continuous heating and stirring, the prepared NC solution is added to the prepared PVA aqueous solution in a certain volume ratio, and stirring is continued to obtain a milky white and blue-light crude emulsion through solvent replacement; Solvent removal: The crude emulsion is added into a rotary evaporator bottle, and the organic solvent in the crude emulsion is removed by the rotary evaporator under reduced pressure to prepare a water-resistant polyvinyl alcohol coating system doped with NC nanoparticles.
2. The method for preparing a water-resistant polyvinyl alcohol coating system according to claim 1, characterized in that: The preparation of PVA aqueous solution is specifically as follows: Add 0.05-0.8 g of polyvinyl alcohol to 10±1 mL of deionized water, dissolve under continuous magnetic stirring at 80-100° C. to form a transparent solution, and allow to cool to prepare a PVA aqueous solution with a concentration of 5 mg / mL-80 mg / mL.
3. A method for preparing a water-resistant polyvinyl alcohol coating system according to claim 1 or 2, characterized in that: In the preparation of the PVA aqueous solution, the stirring speed is 300~500rpm and the stirring time is 3~5h.
4. The method for preparing a water-resistant polyvinyl alcohol coating system according to claim 1, characterized in that: The preparation of NC solution is as follows: 0.2 g of NC was added to 10 ± 1 mL of a mixed solvent of acetone and ethanol with a volume ratio of acetone to ethanol of 10:0 to 2:
8. The solution was continuously stirred magnetically at 300 to 500 rpm for 15 to 30 min to prepare a uniform NC solution with a concentration of 20 mg / ml.
5. A method for preparing a water-resistant polyvinyl alcohol coating system according to claim 1 or 4, characterized in that: In the preparation of NC solution, the nitrogen content of NC is 11.8~12%.
6. The method for preparing a water-resistant polyvinyl alcohol coating system according to claim 1, characterized in that: Emulsification is specifically: At a temperature of 28±1°C and under continuous magnetic stirring at 300~500 rpm, the prepared NC solution was added to the PVA aqueous solution to form an oil-water mixed phase. The volume ratio of the NC solution to the PVA aqueous solution was 1:
1. The oil-water mixed phase was continuously stirred for 20±2 min to obtain a milky white and bluish crude emulsion.
7. The method for preparing a water-resistant polyvinyl alcohol coating system according to claim 1, characterized in that: During solvent removal, The reduced pressure conditions refer to a temperature of 35~40°C and a pressure of -0.098 MPa.
8. A water-resistant polyvinyl alcohol coating system prepared by the method for preparing a water-resistant polyvinyl alcohol coating system according to any one of claims 1 to 7.
9. A method for preparing a water-resistant polyvinyl alcohol nanocomposite film using the water-resistant polyvinyl alcohol coating system according to claim 8, characterized in that: The following steps are involved: The water-resistant polyvinyl alcohol aqueous coating system according to claim 8 is uniformly cast onto a container, and then placed in a water bath oven at 50-60° C. and dried for 24-36 hours.